ADSORPTION OF CU (II) FOR PEARLS CALCIUM ALAGINATE PARTICLES MACROSYSTIS PYRIFERA - Tapia H, Nelson (2008)
It has been obtained bead of calcium alginate with micro-particles of algae Macrosystis Pyrifera. The optimum pH for adsorption of Cu(II) lie between 4,5 and 5. From the study of the kinetics of adsorption was determined that the equilibrium was reached after 400 min. The adsorption data fitted well with the Langmuir model and showed the maximum adsorption capacity qmax= 14,04 mg/g.